1977
DOI: 10.2134/agronj1977.00021962006900030038x
|View full text |Cite
|
Sign up to set email alerts
|

Trickle Irrigation and Fertilization of Tomatoes in Sand Dunes: Water, N, and P Distributions in the Soil and Uptake by Plants1

Abstract: Trickle irrigation has a special advantage in sandy soils where the accurate control of water and ions in the plant's root volume is critical. The purpose of the present work was to investigate the simultaneous migration of water and nutrients from a drip source in the field, to study the plant's response to various moisture and concentration distributions in the soil and to define optimal conditions for maximum yields. Tomato plants (Lycopersicum esculentum Mill.) grown in a field of fine sand received variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 0 publications
3
31
0
2
Order By: Relevance
“…Some potential advantages of fertigation are: improved efficiency of fertilizer recovery (Miller et al 1981, Phene andBeale 1976), minimal fertilizer losses due to leaching (Bresler 1977, Klein et al 1989, Papadopoulos 1985, Stark et al 1983, control of nutrient concentration in soil solution (Bar-Yosef 1977, Papadopoulos 1986 andb;1987b), control of nutrients form and ratio of the various forms particularly for Nfertilizers and flexibility in timing of fertilizer application in relation to crop demand based on development and physiological stage of crops (Bresler 1977). Advantages of scheduling fertilizer applications on the basis of needs are potentially reduced nutrientelement losses associated with conventional application methods that depend on the soil as a reservoir for nutrients.…”
Section: Fertigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some potential advantages of fertigation are: improved efficiency of fertilizer recovery (Miller et al 1981, Phene andBeale 1976), minimal fertilizer losses due to leaching (Bresler 1977, Klein et al 1989, Papadopoulos 1985, Stark et al 1983, control of nutrient concentration in soil solution (Bar-Yosef 1977, Papadopoulos 1986 andb;1987b), control of nutrients form and ratio of the various forms particularly for Nfertilizers and flexibility in timing of fertilizer application in relation to crop demand based on development and physiological stage of crops (Bresler 1977). Advantages of scheduling fertilizer applications on the basis of needs are potentially reduced nutrientelement losses associated with conventional application methods that depend on the soil as a reservoir for nutrients.…”
Section: Fertigationmentioning
confidence: 99%
“…Since chemical characteristics of fertilizers differ, mineral nutrients are differently distributed in the soil when applied by drip irrigation (Bar-Yosef 1977, Papadopoulos 1985. The nitrate form of nitrogen does not react with the soil exchange sites and is not held in soils.…”
Section: Distribution Of Fertilizers Under Drip Fertigationmentioning
confidence: 99%
“…An optimum value of about 140mgNI-1 in the soil solution was deduced for field tomatoes grown in a sandy soil (Bar-Yosef, 1977). For instance, concluded that 100-120mgNOr Nkg-1 was fully adequate for indeterminate tomato plants.…”
Section: Nutrient Levels In the Soilmentioning
confidence: 99%
“…Feigin et al (1982) reported that fertigation (combined irrigation and fertilization) is the most efficient method of fertilizer application. Drip irrigation has gained widespread popularity as an efficient method for fertigation because both time and rate of nutrients can be controlled to meet the requirements of a crop at each physiological growth stage (Bar-Yosef 1977;Papadopoulos 1988;Mmolawa and Or 2000).…”
Section: Introductionmentioning
confidence: 99%